Comparison and Relation Between Vocal Tract Discomfort and Voice Handicap Index in Teachers With and Without Muscle Tension Dysphonia - Seyyedeh Maryam Khoddami; Samira Aghadoost; Ahmad Reza Khatoonabadi; Payman Dabirmoghaddam; Shohreh Jalaie (University of Social Welfare and Rehabilitation Sciences, 2023)
Objective One of the most voice-related complaints in teachers is vocal tract discomfort (VTD) which can increase the voice handicap index (VHI) to different degrees. In teachers Muscle Tension Dysphonia (MTD), increases voice complaints and decreases the voice-related quality of life. The aims of this study were to evaluate and compare the frequency and severity subscales of the VTD score and total score of VHI and determine the relation between them in primary school teachers with and without MTD. Materials & Methods This study was cross-sectional and was performed on 80 primary female teachers with and without MTD. The participants in both groups were randomly selected after checking the inclusion criteria. Voice history, auditory-perceptual assessment of voice, palpation, and laryngeal video-stroboscopy were assessed on the teachers in two groups. Then, asked the participants to complete the Persian versions of the VTD and VHI scales. After determining the normal distribution of the data using the Kolmogorov-Smirnov test, the results of VTD, VHI, and their subscales were compared between two groups with an independent t-test. Also, the relationship between them was assessed with the Pearson correlation coefficient analysis. Results The mean score of the frequency subscale of VTD in teachers with MTD was more than in teachers without MTD (30.17±5.11, 8.22±2.26), respectively. The score of severity subscales of VTD in teachers with MTD was 39.12±4.94 and in teachers without MTD was 7.89±2.13. Also, the total score of the VHI questionnaire in teachers with MTD was significantly higher than teachers without MTD (P<0.05). Moreover, there was a significant positive correlation between the frequency and severity subscales of VTD and the total score of VHI in the two groups (P<0.05). Conclusion This study showed the frequency and severity scores of the VTD and the degree of VHI experienced by MTD are remarkably higher than teachers without MTD. The authors emphasize on the use of VTD and VHI scales in screening teachers who are at risk of voice problems, and the researchers pointed out the importance of paying attention to the reduction of discomfort feelings in the vocal tract and voice handicap in the voice therapy sessions of teachers with MTD.